USE OF MISOPROSTOL FOR INDUCTION OF LABOUR IN UNFAVOURABLE CERVIX - Haider, Gulfareen; Nizam, Khairunnisa (Pakistan Armed Forces Medical Journal, 2011)
Objective: Objective of this study was to determine the maternal and fetal outcome after induction of labour with misoprostol in term pregnancies with unripened cervix. Study Design: Experimental study. Place and Duration of Study: Non probability convenient, in the labour ward of Nawabshah medical college hospital Sindh, Pakistan from 6th April 2008 to 5th Dec 2008. Material and Methods: Total 114 patients were induced with misoprostol who had singleton pregnancy of more than 36 weeks with cephalic presentation, reactive CTG and unfavorable cervix (Bishop Score 4, nonreactive CTG, any contraindication to induction of labour and bishop score > 4 were excluded from the study. After taking an informed consent, patients were given 100mcg misoprostol in posterior fornix of vagina every 6 hour till 3 doses or initiation of labour. Labour was recorded on partogram. Maternal and fetal outcome were recorded on a self designed proforma. Results: Majority of patients i.e. 63(55.2 6%) belonged to age group of 23-30 years. Eighty seven (76.31%) patients who received induction were primigravida while 27(23.68%) patients were P2-P4. Thirty six (31.57%) patients required single dose of misoprostol, 54(47.36%) patients required two doses while 24(21%) patients required three doses. Out of all these 114 patients, labour was successfully completed in 93(81.57%) patients. While cesarean section was done in 21(18.42%) patients. About 48(42.10%) patients were delivered in 8 to 9 hours. Uterine hyper stimulation was seen in 9(7.89%) patients. Apgar score was less than 7 in six (5.26%) newborns. Conclusion: Misoprostol is safe for induction of labour with an unfavorable cervix. The results were satisfying with minimal complications.